CLEPSYDRA @ 37.94578, 23.61960:: AN EPHEMERAL GEOGRAPHIC INSCRIPTION OF POLITICAL PHANTASMATA - PASCHALIDOU, MARIA (Design/Arts/Culture, 2024)
This article discusses the practices and conceptualizations of the Clepsydra @ 37.94578, 23.61960 public mnemonic performance/ in-situ light installation (Lipasmata Drapetsonas, Piraeus, Greece, October 2020). Referring to twenty-one selected cases of lethal political violence in Greece during the years of 1978-2020, Clepsydra @ 37.94578, 23.61960 endeavours to map a traumatic route in time and unveil the political phantasma as a performative geographical inscription questioning traditional forms of mnemonic representation in the urban environment. It incorporates the idea of the ghost as a nomadic (im)materiality that unsettles the linearity of space and time working both as a political mediator and a holder of historical memory but also framing conditions for alternative futures. It seeks to create an archaeology of the political phantasma calling for political awareness against the current rise of neo-fascist movements in Western capitalist societies, and the moving forward by acknowledging and fulfilling the responsibility towards the dead.